Luteolin: A promising natural agent in management of pain in chronic conditions - Ntalouka, Foteini; Tsirivakou, Athina (Frontiers in Pain Research, 2023)
Pain due to chronic conditions is a frequent and insufficiently addressed problem. Current drug options for pain management (either in cases of chronic inflammatory conditions or neuropathy) do not adequately treat pain. Moreover, they are associated with important adverse events in long term use. Luteolin is a flavonoid widely present in the plant kingdom and its sources have been assembled in a comprehensive list of this paper. Luteolin has shown in several research studies a range of pharmacological properties; anti-inflammatory, antioxidant, neuroprotective, and analgesic. In this article, we summarize the effects and potential benefits from introducing luteolin as an adjuvant agent in established protocols for pain management. We review the most indicative in vivo and in vitro evidence of how luteolin can target the molecular pathways involved in pathogenesis of chronic inflammatory and neuropathic pain. The data reviewed strongly support luteolin’s promising benefits in pain management and raise the need for further clinical trials that can establish its role in clinical practice.